Mathematical Understanding Ability And Self Regulated Learning Of Elementary School Students Using Snowball Throwing Approach - Odorlina Marbun; Euis Eti Rohaeti; Rippi Maya ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2021)
This research was motivated by the problem of the low abilities of elementary students to understand mathematical understanding and self-regulated learning (SRL). The purpose of this study was to examine the mathematical understanding ability and SRL of elementary school students who received learning using the Snowball Throwing approach. The research method is a quasi-experimental with the population of all students in private elementary schools in Karawang district. The sample subjects were two classes of fourth grade elementary school students in Karawang, totaling 44 students. The first class with 22 students receive the snowball throwing learning approach and the other 22 students receive regular learning. The instrument used in this research were a test of the mathematical understanding ability on the flat shape material, that consist of 5 essay questions and a self-regulated learning scale that consist of 30 statements. The results showed that the enhancement in the mathematical understanding ability of elementary school students who received learning with the snowball throwing approach was better than the reguler learning, while for Self-Regulated Learning students who received learning using the snowball throwing approach there was no significant difference with students who received regular learning. In addition, there is no correlation between mathematical understanding abilities and students' self-regulated learning.